Meeting the information needs of children in hospital. (December 2013) - Lambert, Veronica; Glacken, Michele; McCarron, Mary
The provision of information is an individual entitlement and a prerequisite to enabling children to understand their illness, make choices about their health care and be involved in decision-making processes around these choices. However, limited evidence exists on children's perspectives of information provision while an inpatient in hospital. The aim of this paper is to describe the process of information exchange between health professionals and children in hospital. Informed by an ethnographic design, data were collected using multiple methods, including semi-participant observations, interviews and participatory activities. Forty-nine children aged six to 16 years, with a variety of medical and surgical conditions, admitted to one children's ward at one children's hospital participated in the research. Findings revealed that children encountered a variety of information management experiences. The key message for health professionals is that there is a need to develop child- and family-focussed strategies for assessing children's information needs in order to determine their preferences for information (amount, format, from whom, etc.), to develop a method for gaining an appreciation of parents' and health professionals' beliefs about the optimal amount and type of information to relay to children, and to achieve consensus about who is best placed to transmit this information to children.